On the modulus of u-convexity of Ji Gao - Eva María Mazcuñán-Navarro (Abstract and Applied Analysis)
We consider the modulus of u-convexity of a Banach space introduced by Ji Gao (1996) and we improve a sufficient condition for the fixed-point property (FPP) given by this author. We also give a sufficient condition for normal structure in terms of the modulus of u-convexity.